Utilização da tecnologia BIM para compatibilização de projetos: análise da casa do estudante João de Barro - (:unkn) unknown (Universidade Federal do Pampa, 2016)
More complex projects, deadlines and reduced costs, in addition to greater demands on the part of the clients, brought to the civil construction several problems that decreases the quality of the works. These problems are related to the incompatibilities in the projects of the buildings, thus causing the necessity of compatibilizing them to appear. In this context, the application of the Building Information Modeling (BIM) platform is a valuable tool because it has features that facilitate this process. Therefore, the present work aims to analyze the design of a building using the methodology BIM, in order to ascertain the different projects involved and to verify if there are divergences between them, with the objective of making them compatible. This work is composed of a theoretical reference, where the concepts of design, the causes and consequences of the incompatibilities, the motivations to be compatible, and the presentation of the compatibilization methodologies including the tool BIM are shown. The methodology used is to model the different projects of the building and to make them compatible in two stages, in which the first consists in the compatibility between the architectural and structural projects, and the second stage is the compatibility between the hydrosanitary project with the architectural and structural projects already Compatible. In the compatibilization between the architectural and structural projects, the detected interferences were divided into two groups: aesthetic interference and technical interferences. Aesthetic interferences are those that only compromise the appearance of the project, requiring no change in the designed systems. The main aesthetic interferences were the protrusions of pillars on walls. The technical interferences are all those that require changes in the projected elements, as they can compromise the performance of the conflicting elements. For these interferences, the main ones were referring to the slabs, being differences between the level of the slabs of the architectural project with slabs of the structural project and lack of openings in the slabs of the structural project for the passage of shafts, which are foreseen in the architectural project. In the compatibilization between the hydrosanitary project with the architectural and structural projects, the main conflicts found, between architecture and hydrosanitary, were the lack of openings in slabs for the passage of shafts and gutters in disagreement with the predicted in the architectural design while the main conflict between the structural project and the hydrosanitary project was between pipes and beams. The use of BIM technology for project compatibilization proved to be efficient, since in the modeling phase it was possible to detect both the existence of conflicts between the projects and the existence of problems in the modeled projects. In the compatibilization stages, some of the existing conflicts could be noticed through a visual analysis of the project, because with the combination of all the projects it is possible to visualize them as a single element, making it possible to easily detect the most obvious conflicts. The methodology proposed to reconcile the architectural, structural and hydrosanitary projects with the use of BIM technology was satisfactory, meeting all the objectives of this work.
Keywords: Engenharia civil; Arquitetura de habitação - Projetos e plantas; Modelagem de informação da construção; Compatibilização; Civil engineering; Architecture of housing - Projects and plans; BIM (Building information modeling); Compatibility; CNPQ::ENGENHARIAS